Answer:
0.00027148092
Step-by-step explanation:
calculator lol
(2/3)x^2 -6x + 15 = 0
Using the quadratic formula:
x = [-b +-sq root(b^2 - 4 *a*c)] / 2a
x= [--6 +-sq root(36 -4*(2/3)*15] / 2*(2/3)
x= [6 +-sq root 36 -40] / (4/3)
x1 = 4.5 + (2i / (4/3))
x1 = 4.5 + 1.5i
x2 = 4.5 - (2i / (4/3))
x2 = 4.5 - 1.5i
Answer:
13
Step-by-step explanation:
Questions with multiple signs are solved using the rule of BODMAS. Which means, Bracket Of Division, Multiplication, Addition and Subtraction.
In the question, we have Bracket, Addition and Subtraction, and will be answered in that order
1-1(0)-55+67
1-0-55+67
1-0+(-55+67)
1-0+(12)
1+12
13